Internal Factors Affecting Green Procurement of Food and Beverage Firms in Vietnam - Giang, Do Huong; Huyen, Le Ngoc Khanh; Trang, Luyen Thu; Giang, Nguyen Quynh; Linh, Tran Phuong (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 1 No 4, 2021)
The main purpose of this study is to explore the internal factors affecting the green procurement of Food and Beverage (F&B) enterprises in Vietnam. The official study was conducted with 235 F&B enterprises operating in Vietnam through direct and online survey methods. The research results have identified five internal factors that directly affect green procurement activities, including: (i) Corporate social responsibility, (ii) Business strategy, (iii) Quality human resources, (iv) Information technology and (v) Management awareness and commitment. In particular, the quality of human resources is the factor that has the most positive and strongest influence on the green procurement activities of enterprises in the F&B industry in Vietnam.